Effect of the Surface Hardening on the Corrosion and Erosion Corrosion of Low Carbon Steel - A. Hassan, Mohammed A. Sadik (Nahrain University College of Engineering Journal, 2014)
This research studied the effect of surface hardening (Carbureting, Nitrating and Nitro-Carbureting) on corrosion and corrosion–erosion of low carbon steel C10E (0.2%C).The surface treatments were carried out to the specimens of the used steel and showed the effect of saline (Bath salt), erosion corrosion suspension on the amount of loss weighted of the surface sample immersed in that mediums.Micro-hardness( Vicker's) test was carried out for all the samples before and after surface treatment (Carbureting, Nitrating and Nitro-Carbureting )Some samples was immersed in bath saline ( 3.5%NaCl ) and others in (3.5%NaCl +SiO2) as aggressive suspensions at different periods of time (3,6,9,15) days .The results of corrosion –erosion tests which were conducted on the samples(the sample upon receipt and after Carbureting, Nitrating and Nitro- Carbureting ) showed the occurrence of corrosion –erosion on the surface of tested sample by loss amount of the surface mass which measured in )mg/cm².day) .The results of testing hade been compared and analyzing the erosion and corrosion by using loss amount of the surface mass which measured in (mg/cm².day).The best performances have shown samples which have been treated with duplex surface treatment (Nitro-Carbureting) as was predicted.